PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA BERWAWASAN DIGITAL PADA UMKM ZAYYAN ART DESIGN PASCA COVID 19 - Hari Sukarno; Susanti Prasetiyaningtiyas; Khanifatul Khusna; Abdul Muhsyi; Alif Mirzania (As-Sidanah, 2022)
The presence of MSME-scale businesses in Indonesia has improved the country's economy, especially during the economic crisis hit, one of which was during the COVID-19 pandemic. This pandemic has also changed the business flow of all business actors, including MSMEs. During the pandemic, all business people who initially only marketed their products conventionally began to take advantage of technological sophistication, especially on social media. The use of social media and technological sophistication is an alternative to develop the existing market potential while making it easier for business actors to find what consumers need. The use of technology is also applied to products produced by MSMEs, one of which is Zayyan Art Design, an MSME actor in the craft sector. One of Zayyan Art's obstacles to running their business is that they can’t use social media to market their products. The purpose of the activities that have been carried out is to help improve skills by increasing the capacity of human resources with a digital perspective. This increase is expected to help increase the number of sales of partner products so that partner problems can be slightly reduced especially in financial problems and an increase in partner income. The method that has been used in this activity is Asset Based Community Development (ABCD). This concept is one of the strategies in service activities whose main activity is community development in the form of training and assistance in using technology in marketing for Zayyan Art. The form of training that has been held is in the form of tutorials on making product marketing videos and making digital product catalogs. The results of the service activities that have been carried out are an increase in employee skills in using social media and expanding the market reach of Zayyan Art products.